Fiber Reinforced Polyimide Aerogel Composites with High Mechanical Strength for High Temperature Insulation. Issue 5 (22nd February 2019) - Zhu, Zhaoxian; Yao, Hongjun; Wang, Fei; Dong, Jinxin; Wu, Kede; Cao, Junxiang; Long, Donghui
Abstract: Glass fiber/polyimide aerogel composites are prepared by adding glass fiber mat to a polyimide sol derived from diamine, 4, 4′‐oxydianiline, p‐phenylene diamine, and dianhydride, 3, 3′, 4, 4′‐biphenyltetracarboxylic dianhydride. The fiber felt acts as a skeleton for support and shaping, reduces aerogel shrinkage during the preparation process, and improves the mechanical strength and thermal stability of the composite materials. These composites possess a mesoporous structure with densities as low as 0.143–0.177 g cm −3, with the glass fiber functioning to improve the overall mechanical properties of the polyimide aerogel, which results in its Young's modulus increasing from 42.7 to 113.5 MPa. These composites are found to retain their structure after heating at 500 °C, in contrast to pure aerogels which decompose into shrunken ball‐like structures. These composites maintain their thermal stability in air and N2 atmospheres, exhibiting a low thermal conductivity range of 0.023 to 0.029 W m −1  K −1 at room temperature and 0.057to 0.082 W m −1  K −1 at 500 °C. The high mechanical strengths, excellent thermal stabilities, and low thermal conductivities of these aerogel composites should ensure that they are potentially useful materials for insulation applications at high temperature. Abstract : Glass fiber/polyimide aerogel composites are prepared by adding glass fiber mat to a polyimide sol derived from diamine and dianhydride. The microstructure of the aerogels prepared can be regulated by using different diamine formulations. The composites occupy typical three‐dimensional nanostructure.